Assessing Country Risk : Selected Approaches - Ahuja, Ashvin (Technical Notes and Manuals; Technical Notes and Manuals ;, 2017)
Assessing country risk is a core component of surveillance at the IMF. It is conducted through a comprehensive architecture, covering both bilateral and multilateral dimensions. This note describes some of the approaches used internally by Fund staff to examine a wide array of systemic risks across advanced, emerging, and low-income economies. It provides a high-level view of the theory and methodologies employed, with an on-line companion guide providing more technical details of implementation. The guide will be updated as Fund staff's methodologies for assessing country risk continue to evolve with experience and feedback. While the results of these approaches are not published by the IMF for market sensitivity reasons, they inform risk assessments featured in bilateral surveillance as well as in the IMF's flagship publications on global surveillance.